KASEKTEN PEREMPUAN DI PESANTREN: PONDOK PESULUKAN THORIQOT AGUNG TULUNGAGUNG - Ravika Alvin Puspitasari; Budi Harianto (Institut Agama Islam Negeri Ponorogo, 2021)
In Javanese Islamic discourse in general, Javanese scholars look more at the broad horizon of Sufistic teachings and practices as an important variable in the Islamization of Java. The author feels that the micro area that discusses daily spirituality, especially women's spirituality, is an area of study that is worthy of research. In the practice of spirituality, of course, it cannot be separated from magical power, it is believed to have supernatural powers. The power is obtained in practice or penijazahan. Then there are various theories about mysticism, kebatinan to sects, in fact women are also actively involved in cosmology or social facts in Java. Therefore, the author poses a research question, namely, why the position of women in the narrative of daily spirituality is considered secondary and how is the practice of kasekten in Pondok Pesulukan Tharekat Agung. This paper specifically discusses the practice of spirituality or female students at the Thoriqot Agung Islamic boarding school in Tulungagung district. Practice or education is generally known as the path that can lead a person to gain enlightenment (sakti). This study uses an ethnographic-based qualitative approach. The findings of this study explain that sociological aspects and patriarchal religious interpretations condition women's spirituality to always be at a secondary level. Women who engage in spiritual practice cannot get the same degree as men, such as becoming Murshid, even though they are already spiritually established. Thus, women are only counted as students in the Tarekat and are not as charismatic as men who hold the title of Kyai Tarekat.Keyword: Kesakten; Spiritual; Women; Secondary